Cognitive Conflict-Based E-Book with Real Experiment Video Analysis Integration to Enhance Conceptual Understanding of Motion Kinematics - Mufit, F.; Asrizal, A.; Puspitasari, R.; Annisa N, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Students find it challenging to understand motion concept or mechanics in physics learning and often experience misconceptions. There is also a lack of teaching materials that promote conceptual understanding. This study aims to produce a valid, practical, and effective e-book based on cognitive conflict to enhance conceptual understanding. This research used explanatory sequential mixed methods. The effectiveness test was carried out through an experimental method with a pretest-posttest control group design. Using the cluster random sampling, 61 science students performed as the samples. The research instruments used were interview guides, observation sheets, questionnaires, and two-level multiple-choice concept tests. The data were analyzed qualitatively and quantitatively using Aiken's V formula, the percentage technique, and the Mann-Whitney hypothesis test. This study produced an e-book according to the four syntaxes of the cognitive conflict-based learning model (CCBL). Real experiment video analysis was integrated into the third syntax. The e-book is valid in content, construct, language, and graphics, with an average of 0.83 in the high category. This e-book is practical in terms of user convenience, attractiveness, and benefits, with an average of 79.6 in the strong category. This e-book is effective, with a significant effect of 0.001 0.05 on conceptual understanding and misconceptions. We concluded that the cognitive conflict-based e-book with real experiment video analysis integration is valid, practical, and effective in enhancing students' conceptual understanding of motion kinematics.